Streptococcal toxic shock-like syndrome: evidence of superantigen activity and its effects on T lymphocyte subsets in vivo. - Michie, C; Scott, A; Cheesbrough, J; Beverley, P; Pasvol, G (1994)
Toxic shock-like syndrome is a serious complication of invasive streptococcal disease. The syndrome is believed to be the consequence of exposure to exotoxins produced by the infecting organisms which behave as superantigens. We describe two patients who fulfilled clinical criteria for this syndrome, one of whom died. Streptococci isolated from both patients were found to produce a mitogen specific for the V beta 2+ T lymphocyte subset in vitro, which had the characteristics of a superantigen. The phenotype and function of lymphocytes collected from both patients during the acute phase of their illness demonstrated a marked reduction in circulating CD4+ ('helper') and CD45RA+ ('naive') T lymphocytes expressing the V beta 2 chain, and an increase of those expressing CD8, CD45RO and the V beta 2 chain. This effect resolved within 4 weeks in the patient who survived. Proliferation assays demonstrated no T cell anergy in either patient. Stimulation of lymphocytes by superantigen in these clinical situations does not appear to cause permanent deletion of T cell subsets, as has been observed in animal models.